2007
DOI: 10.1002/esp.1515
|View full text |Cite
|
Sign up to set email alerts
|

Dust emission from wet and dry playas in the Mojave Desert, USA

Abstract: The interactions between playa hydrology and playa-surface sediments are important factors that control the type and amount of dust emitted from playas as a result of wind erosion. The production of evaporite minerals during evaporative loss of near-surface ground water results in both the creation and maintenance of several centimeters or more of loose sediment on and near the surfaces of wet playas. Observations that characterize the texture, mineralogic composition and hardness of playa surfaces at Franklin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
176
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(191 citation statements)
references
References 55 publications
5
176
0
Order By: Relevance
“…The mineralogical data published by [27] were sampled in 1991 and 1992. During this >20 year time frame the surface alteration, e.g., by redistribution of surface particles due to surface flooding [15] and or wind erosion [9] are possible scenarios. The formation of fresh halite crust after significant rainfall and flooding events may superimpose underlying less soluble (e.g., clastic) minerals [110] and hide these (minor) components from surface observations, especially in the central halite dominated, dynamic part of the salt pan.…”
Section: Pan Surface Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…The mineralogical data published by [27] were sampled in 1991 and 1992. During this >20 year time frame the surface alteration, e.g., by redistribution of surface particles due to surface flooding [15] and or wind erosion [9] are possible scenarios. The formation of fresh halite crust after significant rainfall and flooding events may superimpose underlying less soluble (e.g., clastic) minerals [110] and hide these (minor) components from surface observations, especially in the central halite dominated, dynamic part of the salt pan.…”
Section: Pan Surface Characterisationmentioning
confidence: 99%
“…Although the area of individual salt pans is small, mostly less than a few square kilometers, except for prominent examples such as Salar de Uyuni (Bolivia) or Etosha pan (Namibia), the study of salt pan is important because of increasing population, agricultural demand and the hydrology of these dry regions becoming greatly stressed [4]. Salt pans are also one of the biggest sources of mineral dust emission in arid regions [5,6] especially in the southern Africa Kalahari desert (Botswana, Namibia, and Republic of South Africa) [7] and the specific salt pan mineralogy influences the susceptibility for dust emission [8][9][10]. For continued advances in understanding dust sources a spatially and temporally detailed assessment of their surface sediments is necessary [11].…”
Section: Introductionmentioning
confidence: 99%
“…The higher diversity of dust fluxes presents morphological disparity and sedimentological diversification in test areas. That dust emissions are highly variable with space and between distinct landforms, even within individual landforms, may be caused as a result of aeolian processes (Gill, 1996;Reynolds et al, 2007). It may also be related to dust fluxes not coming from a similar saturation from a field site (Gillette and Passi, 1988).…”
Section: The Effect Of Trampling On Dust Emissionsmentioning
confidence: 99%
“…Though many dry and drying lakes, whether natural (e.g., Australia's Lake Eyre, Chad's Bodélé Depression) or manmade (e.g., California's Owens Dry Lake, central Asia's Aral Sea), are significant sources of dust, research has shown that not all dry lakes are dust sources or, at least, not all the time [Reynolds et al, 2007]. One consequence of this generalization is the notion that nonlake sources are not significant.…”
Section: Where Does Dust Come From?mentioning
confidence: 99%